Hubungan Pengetahuan, Sikap dan Iklan Susu Formula dengan Pemberian ASI Ekslusif di Wilayah Puskesmas Rawat Inap Cempaka Kota Banjarbaru - Netty Netty; Nurul Indah Qariati; Siti Rabiathul (Jurnal Kesehatan Indonesia, 2019)
Exclusive breastfeeding rate in South Kalimantan is only 51.18% of what should be 70%. Factors that inhibit exclusive breastfeeding are the lack of mother's knowledge of exclusive breastfeeding excellence, mother's attitude towards exclusive breastfeeding, and incessant milk formula advertising. The aim of this research is to know the relationship of knowledge, attitude and advertising of formula milk with Exclusive Breast Feeding in Cempaka Rawat Inap Puskesmas of 2018. Method of research of analytic survey with cross sectional approach. The population is all mothers who have babies aged 6-24 months which amounted to 435 people. Sample of 81 people. Sampling using technique Purposive sampling. The statistical test is Chi square test. The results showed that the most breastfeeding was not exclusive breastfeeding as much as 42 people (51.9%). Knowledge of respondents at most is quite as much as 43 people (53.1%). The most positive attitude is 46 people (56.8%). Infant formula advertising in mothers showed that most respondents were interested in formula milk ads as much as 48 people (59.3%). There is knowledge relation (p-value = 0,012 <α 0,05), there is relationship of attitude (p-value = 0,000 <α 0,05). There is a formula milk advertising relationship (p-value = 0,000 <α 0.05). It is hoped that mothers can increase their knowledge, awareness about the importance of exclusive breastfeeding, and are not interested in formula milk advertising despite offering attractive promotions and prizes